Mental Health Service Use Among Depressed, Low-Income Homebound Middle-Aged and Older Adults - Choi, Namkee G.; Kunik, Mark E.; Wilson, Nancy (Journal of aging and health, 2013)
Objectives: This study examined previous mental health service use among low-income homebound middle-aged and older adults who participated in a study testing the feasibility and efficacy of telehealth problem-solving therapy for depression. Method: The sample consisted of 188 homebound adults aged 50 years or older. Data on mental health service use were collected at baseline. We used multivariable logistic regression analysis to examine correlates of different types of outpatient service use within the preceding 12 months. Results: Of the subjects, 56% reported mental health service use. Of the users, 80% had made at least one primary care mental health visit, 21% had visited a psychiatrist, and 25% had received counseling. Higher depressive symptom severity scores were positively associated with a psychiatrist visit only. Discussion: The need to improve low-income homebound older adults’ access to psychotherapy was clearly evident.